Power Quality and Harmonics Management in Modern Power Systems (IntechOpen eBooks, 2024)
This book comprehensively tackles the challenges and solutions related to power quality and harmonics management in modern power systems. It covers many topics, beginning with the significance of maintaining power quality in the presence of distributed generation and power electronic-based technologies. It explores the impact of nonlinear loads and novel equipment on power quality and emphasizes its significance in a competitive energy environment. The book also discusses renewable-based distributed generation and hosting capacity studies. Another key focus of the book is the impact of harmonics on electrical networks. It highlights the consequences of harmonics generated by electronic devices and emphasizes the need for control and mitigation measures. The distinction between linear and nonlinear loads is explained, and fundamental indicators of electrical harmonics are discussed. The book provides insights into frequency domain models of nonlinear loads in power systems, emphasizing the importance of understanding and modeling harmonics. It also evaluates the effectiveness of active filters in mitigating power system harmonics and explores the performance efficiency of the shunt hybrid system. Furthermore, the book offers a multidisciplinary perspective on energy security in the face of climate change and growing uncertainties. It examines energy security from various angles and advocates for integrating resilience thinking into energy security policies. Finally, this book provides a foundation for understanding and addressing the challenges associated with power quality and harmonics in modern power systems, offering practical approaches and solutions to enhance system performance and reliability.